COLLEGE GENERAL EDUCATION SCIENCE: CLASSROOM-LABORATORY FACILITIES FOR A PROGRAM. - Fraser, Thomas P. (Science Education, 1968)
The article presents information on the steps taken to improve general education in science at the Morgan State College. The ideal curricular structure should develop not only an understanding of the significant concepts in science but also the ability to apply these understandings in the solution of specific problems. The development of the program at Morgan is characterized by Survey Courses, "Block and Gap" Courses and "Block-and-Bridge" Courses. The college developed facilities for instruction and research in problems of collegiate general education science, such as a large, air-conditioned amphitheater; a "classroom-laboratory" for earth science; a seminar room; faculty and departmental offices and hall-mounted bulletin board and display cases. As part of the program "classroom-laboratory" containing 696 square feet of area, and seating 40 students was constructed for the physical science section of the course organized around concepts in astronomy and geology. While developing the program it was kept in mind that there are ample opportunities for teacher-student interaction, together with some involvement of the student in the actual doing of science rather than reading about it.